Le séminaire de Jacques Lacan. Livre III Les psychoses 1955-1956 - Lacan, Jacques, 1901-1981; Miller, Jacques-Alain, 1944- (S.l. : Éditions du Seuil, 1981)
Lacan besteedt in dit boek aandacht aan de psychose.